The role of the lysosome in natural killing: inhibition by lysosomotropic vital dyes. - Shau, H (1984)
Recent evidence has indicated the importance of lysosomes in natural killing (NK). The lysosomotropic dye neutral red, at concentrations greater than 2 X 10(-5) M, inhibits NK activity of large granular lymphocytes (LGL). Inhibition is at the level of effector cell activity rather than target cell susceptibility. Neutral red inhibits NK activity without affecting the viability of the effector cell population or the response of lymphocytes to the mitogen, phytohaemagglutinin (PHA). While the mechanism of this inhibition is unknown, neutral red-treated peripheral blood lymphocytes (PBL) do not suppress untreated effector cell populations. Furthermore, neutral red does not influence the binding of effector cells to target cells. Since natural killing by neutral red-treated PBL recovers slowly upon incubation of the cells at 37 degrees, inhibition is not due to selective toxocity. Trypan blue, another frequently used lysosomotropic vital stain, has no effect when effector cells are pretreated with 10(-3) M dye for 30 min or less. However, effector cells first treated with neutral red lose red granular staining following treatment with trypan blue for as little as 10 min at room temperature. Natural killing by neutral red pretreated PBL also recovers more quickly following brief incubation with trypan blue. Treatment of effector cells with trypan blue and neutral red simultaneously prevents accumulation of neutral red in cytoplasmic granules and subsequent inhibition of NK.